Understanding youth athletes` readiness for competition: A review of literature and best practices for coaches and parents - Klinger, B. (The College at Brockport, State University of New York, 2018)
In today`s society, youth sport is a popular social practice, with about 75% of families with elementary aged children participating. However, while many of these children enjoy playing and being active, not all children are ready to participate in a competitive sport environment. Indeed, current youth trends are to start competitive athletics earlier and to specialize in one sport year round, which can cause injury and burnout. Currently, 70 percent of youth athletes stop playing sports at the age of 13, which is a discerning number. The purpose of this study is to provide a comprehensive background on the development of children to determine their readiness for competition and youth sport. Specifically, this study will review the physical, cognitive, and biological factors in child development, and factors influencing psychological and sociological behaviors during competition. Best practices for developing youth athletes will be provided to help to determine youth sport readiness.